Entrepreneurial Intention of Management Students In Pokhara University - Paudel , Bal Chandra; Ranabhat, Deepesh (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: Entrepreneurship plays a vital role in economic development. This study investigated the factors influencing entrepreneurial intention among management students in Nepalese universities.Methodology: With a quantitative approach employing a descriptive and analytical research design, the study encompasses a sample of 225 students from Pokhara University Colleges in Pokhara.Finding and Conclusion: The study found a positive inclination towards entrepreneurship among the surveyed individuals, with a significant proportion expressing confidence in their knowledge and skills for entrepreneurial endeavors. The measurement scale on entrepreneurial intention encompasses various constructs such as entrepreneurial education, attitude, self-efficacy, subjective norms, risk-taking behavior, and intention. The structural equation modeling results showed entrepreneurial selfefficacy, risk-taking behavior, and subjective norms demonstrate significant positive impact on entrepreneurial intention. This study concludes that students who are more confidents, take more risks and have support from their family as well as friends circle tend to launch their business in a confident way. Implications: The study contributes to a comprehensive understanding of factors influencing entrepreneurial intentions among management students in Nepalese universities. These insights provide a solid foundation for informed policymaking as well as offer practical implications for educators, policymakers, and stakeholders involved in promoting entrepreneurship and economic development in the region.